Pengaruh Orientasi Pasar Dan Inovasi Produk Terhadap Keunggulan Bersaing Keripik Pisang Tunas Kota Metro - Berliana Ajeng Pratiwi; Fitriani; Durotun Nasikah (Jurnal Manajemen DIVERSIFIKASI, 2025)
Business in Indonesia is becoming more competitive as a direct result of the country's rapid economic growth. Companies here must improve their capabilities to compete in the global market. Micro and small industries contributed 47.37% to GDP and 93.8% to employment capacity in 2018, according to the Ministry of Cooperatives and SMEs. The food sector is the most common and widespread of the many businesses that may be run in Indonesia. Metro City is an important hub for banana chip production in Lampung Province. Banana-flavored chips are one of the products. Pak Bambang and his wife utilized existing assets by processing bananas with a new and interesting method to make traditional Lampung banana chips. Market orientation (X1), product innovation (X2), and competitive advantage (Y) are variables used in positivist research designs applied to certain populations or random samples. Research findings prove that Tunas Banana Chips in Metro City benefit from the company's market orientation, product innovation, orientation variables, and competitive advantage.